Ambagan 2009 mga salita mula sa iba't ibang wika sa Filipinas - Zafra, Galileo S. (Diliman, Quezon City University of the Philippines Press, 2010)
Compilation of vocabulary words from different dialects in the Philippines.
Includes bibliographical references.
In Tagalog.
Keywords: Philippine language -- Dialects -- Glossaries, vocabularies, etc